Pengaruh Literasi Keuangan Digital, Keamanan, Persepsi Kemudahan Penggunaan dan Reward Terhadap Niat Menggunakan Dompet Digital - Arif Rahman; G.A. Sri Oktaryani (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effect of digital financial literacy, security, perceived ease of use, and rewards on the intention to use digital wallets in Mataram University students. This research uses a quantitative approach with a causal associative method. A sample of 100 respondents was obtained through purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The results of the analysis show that security and reward have a positive effect on the intention to use a digital wallet, while digital financial literacy and perceived ease of use do not have a significant effect on the intention to use a digital wallet. These findings indicate that students consider more aspects of system security and direct benefits offered, compared to aspects of literacy or technical perceptions in deciding to use digital wallets. The practical implications of this study indicate the importance for digital wallet service providers to continue to strengthen the security system and develop reward programs that suit the preferences and needs of the younger generation.